2015
DOI: 10.1136/bmj.h4451
|View full text |Cite|
|
Sign up to set email alerts
|

Safety and efficacy of digoxin: systematic review and meta-analysis of observational and controlled trial data

Abstract: ObjeCtiveTo clarify the impact of digoxin on death and clinical outcomes across all observational and randomised controlled trials, accounting for study designs and methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
208
1
25

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 282 publications
(249 citation statements)
references
References 107 publications
(162 reference statements)
5
208
1
25
Order By: Relevance
“…As demonstrated in this study and others,1, 9, 14 in patients with HF, digoxin is prescribed to patients with more advanced HF, lower LVEF, worse New York Heart Association functional class, and greater burden of other comorbidities. As such, the association between digoxin use and clinical outcomes in patients with HF may be biased by residual confounding caused by the baseline medical condition and concomitant medications 15. Adjusting for multiple confounders, propensity matching, and IPTW may not fully account for this difference.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As demonstrated in this study and others,1, 9, 14 in patients with HF, digoxin is prescribed to patients with more advanced HF, lower LVEF, worse New York Heart Association functional class, and greater burden of other comorbidities. As such, the association between digoxin use and clinical outcomes in patients with HF may be biased by residual confounding caused by the baseline medical condition and concomitant medications 15. Adjusting for multiple confounders, propensity matching, and IPTW may not fully account for this difference.…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting data exist regarding adverse outcomes that are associated with digoxin use in patients with AF 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16. While several retrospective studies and meta‐analyses have demonstrated an association between digoxin use and all‐cause mortality, cardiovascular death, and sudden cardiac death (SCD),6, 7, 8, 9, 10, 11, 12, 13 other studies have not found a compelling association 14, 15, 16.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…W praktyce klinicznej często przepisuje się digoksynę, ale nie przeprowadzono bezpośrednich porównawczych RCT u pacjentów z AF. W metaanalizie badań obserwacyjnych digoksyna wywierała neutralny wpływ na umieralność u pacjentów z AF i współistniejącą niewydolnością serca [badania obserwacyjne skorygowane względem ryzyka: ryzyko względne (RR) 0,90; 95% CI 0,70-1,16; badania obserwacyjne z doborem z wykorzystaniem skali skłonności: RR 1,08; 95% CI 0,93-1,26) [225]. Początkowe i skojarzone leczenie w celu kontroli częstości rytmu komór u pacjentów z AF i HFrEF powinno więc być wybierane z uwzględnieniem charakterystyki poszczególnych chorych oraz występujących u nich objawów.…”
Section: Pacjenci Z Migotaniem Przedsionków Oraz Niewydolnością Sercaunclassified
“…Nie przeprowadzono żadnych bezpośrednich porównawczych RCT, w których oceniono by digoksynę u pacjentów z AF [546]. W badaniach obserwacyjnych wiązano jej stosowanie ze zwiększoną umieralnością wśród pacjentów z AF [547][548][549], ale ten związek wynikał prawdopodobnie z błędów doboru i odmiennej charakterystyki pacjentów, którym przepisywano ten lek, a nie z rzeczywistej szkodliwości digoksyny [550][551][552][553], zwłaszcza dlatego, że digoksynę często stosuje się u ciężej chorych pacjentów [225]. W krzyżowej próbie klinicznej w celu oceny mechanizmów działania, przeprowadzonej w grupie 47 pacjentów z HFrEF i AF, nie stwierdzono różnic pod względem częstości rytmu komór, ciśnienia tętniczego, dystansu chodu i LVEF między leczonymi karwedilolem a leczonymi digoksyną, choć podawanie beta-adrenolityku wiązało się z większym stężeniem peptydu natriuretycznego typu B, to podczas skojarzonego leczenia karwedilolem i digoksyną nastąpił wzrost LVEF, a odstawienie digoksyny spowodowało zmniejszenie LVEF [554].…”
Section: Naparstnicaunclassified